2014
DOI: 10.1117/1.jbo.19.10.101504
|View full text |Cite
|
Sign up to set email alerts
|

Specific tumor labeling enhanced by polyethylene glycol linkage of near infrared dyes conjugated to a chimeric anti-carcinoembryonic antigen antibody in a nude mouse model of human pancreatic cancer

Abstract: Abstract. Labeling of metastatic tumors can aid in their staging and resection of cancer. Near infrared (NIR) dyes have been used in the clinic for tumor labeling. However, there can be a nonspecific uptake of dye by the liver, lungs, and lymph nodes, which hinders detection of metastasis. In order to overcome these problems, we have used two NIR dyes (DyLight 650 and 750) conjugated to a chimeric anti-carcinoembryonic antigen antibody to evaluate how polyethylene glycol linkage (PEGylation) can improve specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Images were obtained at the time points indicated, with fixed exposure times where noted. Signal intensity and specificity are clearly illustrated, and are consistent with previous reports demonstrating in vivo CEA detection, particularly with fluorescently labeled antibodies [ 72 81 ]. In addition to fixed exposure times, automatic exposures were obtained for the 600-640nm excitation on the dorsal side of mice in group 3, and the average exposure time at different points in the study is plotted in Fig 10 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Images were obtained at the time points indicated, with fixed exposure times where noted. Signal intensity and specificity are clearly illustrated, and are consistent with previous reports demonstrating in vivo CEA detection, particularly with fluorescently labeled antibodies [ 72 81 ]. In addition to fixed exposure times, automatic exposures were obtained for the 600-640nm excitation on the dorsal side of mice in group 3, and the average exposure time at different points in the study is plotted in Fig 10 .…”
Section: Resultssupporting
confidence: 89%
“…In addition, a majority of paclitaxel ADCs previously reported couple paclitaxel to antibodies which also exhibit some cytotoxic effects [ 56 59 ]. Although CEA is an effective target for immunofluorescent diagnostics (Figs 3 – 5 ) and visualization of tumors [ 66 81 ], we have demonstrated that CEA antibodies alone do not contribute to cytotoxicity ( Fig 6 ), likely due to the fact that CEA is not necessary for cell survival [ 60 , 61 ]. Further, drug-free antibody control samples (α-CEA-680, IgG-680) exhibited no decrease in cell survival even after prolonged incubation times ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the initial fluorescence at the liver, the signal rapidly decreases after 12 hours and returns close to baseline near 48 hours and beyond. The addition of polyethylene glycol (PEG) groups or attachments of the fluorophore in a conformation that may mask the hydrophobic moieties, could be approaches to improve this issue which will be addressed in future work (28).…”
Section: Discussionmentioning
confidence: 99%
“…Conjugation of molecules with polyethylene glycol (PEG), known as PEGylation, affects the biodistribution of the molecule and is widely used in pharmacology [22]. Maawy et al demonstrated that PEGylation of two NIR antibody-dye conjugates increased the half-life, favorably altered biodistribution, and significantly increased the tumor to background contrast in liver and lung lesions [23]. PEGylated dyes had significantly lower accumulation in the liver when compared to non-PEGylated dyes, and this enabled high contrast imaging of metastatic tumor lesions of the liver [24].…”
Section: Development Of Tumor Selective Fluorescence Labelingmentioning
confidence: 99%